STUDI EKSPERIMENTAL KERUNTUHAN RANGKA KUDA-KUDA BAJA RINGAN PADA ATAP RUMAH DAN SEKOLAH - Utomo, Adityo Budi; Satyarno, Iman; Muslikh, Muslikh (Wahana Teknik Sipil: Jurnal Pengembangan Teknik Sipil, 2020)
Increasingly expensive price of quality woods and difficulties of workmanship, it makes people switch from wood to lightweight steel as a roof truss. The use of lightweight steel as truss becomes popular because of the fast workmanship dan durability of the material. Many cases show that lightweight steel truss at school and house collapsed and caused a fatality. This lightweight steel truss study was carried out on a full scale with a span of 6 m and a slope of 300, while the loading test pattern at the placement points of battens was like truss in the community. The goals of this study to measure and observe several parameters including weight, maximum capacity, stiffness, ductility, price, length of work, and failure pattern. From testing, the result shows that lightweight steel truss has dead weight, maximum capacity, stiffness value, ductility value, price, working time, and failure pattern respectively of 21,3 kg,734 kg, 91,18 kg/mm, 2,97, Rp 1.740.000, 2 days, and failure pattern is buckling on the diagonal top chord. The result of this research indicates that lightweight steel truss can be used in the community with the limitation of using metal roof coverings instead of concrete or ceramic and the distance between the truss max 1,2 m.